Successful on-ECLS Repair of CDH and Omphalocele in a Newborn - Fideler, Frank; Mustafi, Migdad; Kirschner, Hans-Joachim; Gerbig, Ines; Fuchs, Jörg; Hofbeck, Michael; Kumpf, Matthias; Kagan, Oliver; Michel, Jörg; Jost, Walter; Neunhoeffer, Felix (European Journal of Pediatric Surgery Reports, 2023)
Both congenital diaphragmatic hernias (CDHs) and omphaloceles show relevant overall mortality rates as individual findings. The combination of the two has been described only sparsely in the literature and almost always with a fatal course. Here, we describe a term neonate with a rare high-risk constellation of left-sided CDH and a large omphalocele who was successfully treated on extracorporeal life support (ECLS). Prenatally, the patient was diagnosed with a large omphalocele and a left CDH with a lung volume of ∼27% and an observed to expected lung-to-head ratio of 30%. Due to respiratory insufficiency, an ECLS device was implanted. As weaning from ECLS was not foreseeable, the female infant underwent successful surgery on ECLS on the ninth day of life. Perioperative high-frequency oscillatory ventilation and circulatory and coagulation management under point-of-care monitoring were the main anesthesiological challenges. Over the following 3 days, ECLS weaning was successful, and the patient was extubated after another 43 days. Surgical treatment on ECLS can expand the spectrum of therapy in high-risk constellations if potential risks are minimized and there is close interdisciplinary cooperation.
Keywords: CDH and omphalocele; On-ECLS repair; newborn surgery